IgG Antibody Responses to the Aedes albopictus 34k2 Salivary Protein as Novel Candidate Marker of Human Exposure to the Tiger Mosquito - Buezo Montero, Sara; Gabrieli, Paolo; Montarsi, Fabrizio; Borean, Alessio; Capelli, Stefano; De Silvestro, Giustina; Forneris, Federico; Pombi, Marco; Breda, Antonio; Capelli, Gioia; Arcà, Bruno (Frontiers in Cellular and Infection Microbiology, 2020)
Mosquitoes of the Aedes genus transmit arboviruses of great importance to human health as dengue, chikungunya, Zika and yellow fever. The tiger mosquito Aedes albopictus can play an important role as arboviral vector, especially when Aedes aegypti is absent or present at low levels. Remarkably, the rapid worldwide spreading of the tiger mosquito is expanding the risk of arboviral transmission also to temperate areas, and the autochthonous cases of chikungunya, dengue and Zika in Europe emphasize the need for improved monitoring and control. Proteomic and transcriptomic studies on blood feeding arthropod salivary proteins paved the way toward the exploitation of genus-specific mosquito salivary proteins for the development of novel tools to evaluate human exposure to mosquito bites. We previously found that the culicine-specific 34k2 salivary protein from Ae. albopictus (al34k2) evokes specific IgG responses in experimentally exposed mice, and provided preliminary evidence of its immunogenicity to humans. In this study we measured IgG responses to al34k2 and to Ae. albopictus salivary gland protein extracts (SGE) in individuals naturally exposed to the tiger mosquito. Sera were collected in two areas of Northeast Italy (Padova and Belluno) during two different time periods: at the end of the low- and shortly after the high-density mosquito seasons. Anti-SGE and anti-al34k2 IgG levels increased after the summer period of exposure to mosquito bites and were higher in Padova as compared to Belluno. An age-dependent decrease of anti-saliva IgG responses was found especially in Padova, an area with at least 25 years history of Ae. albopictus colonization. Moreover, a weak correlation between anti-saliva IgG levels and individual perception of mosquito bites by study participants was found. Finally, determination of anti-al34k2 IgG1 and IgG4 levels indicated a large predominance of IgG1 antibodies. Overall, this study provides a convincing indication that antibody responses to al34k2 may be regarded as a reliable candidate marker to detect temporal and/or spatial variation of human exposure to Ae. albopictus; a serological tool of this kind may prove useful both for epidemiological studies and to estimate the effectiveness of anti-vectorial measures.